Effect of some concentrations of plant extracts in growth and yield of pea (Pisum sativum L.) (Journal of the College of Basic Education, 2022)
The biological experiment was studied the effect of two concentration 10% and 30% of Rosmarinus officinalis , Lippia citriodora and Laurus noblis on growth and yield component of pea Pisum sativium L . The results showed that plant extract effect signi ficartlyin the height of plants , number of leaves , surface area of leaf , leaf area index , leaf area relative , biological harvest , harvest index and percentage of carbohydrates in seeds .